Pengembangan Media Gambar Komik Mengenai Masalah Gizi Yang Terjadi Pada Anak SD - Matondang, Aflah Husnaini; Purba, Atikah Zahrani; Purba, Hilda Melani; Sabina, Irlyanova; Jannah, Miftahul; Hutasuhut, Riska Fadhilah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In this research, researchers will create a learning development media, namely a comic, which will discuss nutritional problems that occur in elementary school children. In Indonesia, knowledge about balanced nutrition, especially for children, is still low. This means that Indonesia is still facing nutritional problems which can result in malnutrition, stunting, excess nutrition and obesity. Because nutrition education must be provided starting from an early age. In providing nutrition education, the role of the media is very important to help convey the message to the target (students). The media that researchers created to convey nutrition education is comic media. The aim of this research is to find out nutritional problems or disorders that are often experienced by students. Such as the unhealthy habit of snacking out in elementary school children, which can cause health problems such as stomach ache (diarrhea), poisoning, and so on, the lack of understanding and awareness of children about the negative impacts of the habit of snacking out, the absence of or the lack of education and nutrition education programs related to the dangers of snacking outside for elementary school children. A review using a systematic literature review was carried out to analyze information from several selected journals that researched nutritional disorders in elementary school children, and the influence of comic media for delivering education about nutrition. According to the researcher, the media used by the researcher is good and clear, and also the media created by the researcher is valid/suitable for the problem being taken. According to researchers, by using comic media, students will be more effective and enthusiastic when listening to explanations of this problem.